2014
DOI: 10.1590/1677-3225v13n4a05
|View full text |Cite
|
Sign up to set email alerts
|

Force decay in orthodontic elastomeric chains after immersion in disinfection solutions

Abstract: Aim:To evaluate the force decay of orthodontic elastomeric chains after immersion in disinfecting solutions. Methods: One-hundred and fifty segments of elastomeric chains were divided in 3 groups: Control group -no disinfection; Chlorhexidine group -disinfection in 0.12% chlorhexidine digluconate solution; and Peracetic acid group -disinfection in 0.2% peracetic acid solution. Elastomeric chains of 14 mm were stretched up to 20 mm and the given force (kgf) was evaluated in an Instron universal testing machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The main advantage is the ease of use, less bulk and patient comfort (17). In contrast, chains have some drawbacks such as: inability of producing light-continuous force which is the ideal force for tooth movement; and force decay (18). Degradation, rupture and force cut off are always probable (19) and one of the main problems is the periodontal and gingival concerns because of poor hygiene (20).…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage is the ease of use, less bulk and patient comfort (17). In contrast, chains have some drawbacks such as: inability of producing light-continuous force which is the ideal force for tooth movement; and force decay (18). Degradation, rupture and force cut off are always probable (19) and one of the main problems is the periodontal and gingival concerns because of poor hygiene (20).…”
Section: Discussionmentioning
confidence: 99%
“…13 Polyurethane elastic chains and ligatures are subject to contamination, but spool dispensers for chains, ligature assembly for the treatment of a single patient, and cold sterilization are ways of reducing this (Fig 2B ); unfortunately, elastic chains and ligatures are not heat resistant and their repeated disinfection can accelerate the destruction of the cross-links of polyurethane polyesters. 3,4 Recently, Losito et al 14 reported that immersion in chlorhexidine solution (0.12% for 10 minutes) or peracetic acid solution (0.2% for 30 minutes) has no significant effect on the degradation of elastic chains.…”
Section: Orthodontic Instruments and Supplies: Are They Semicritical Or Critical Items?mentioning
confidence: 99%
“…The orthodontics elastomeric chain is polyurethane elastomer that widely used among orthodontists. 1,2 It is a long chain with an interconnected hole, and available in various colors. 3 Due to its elastic ability, orthodontics elastomeric chain can return to its original dimensions when subjected to deformation forces.…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to its elastic ability, orthodontics elastomeric chain can return to its original dimensions when subjected to deformation forces. 2,4 Orthodontics elastomeric chain are used in any movement that requires pulling, such as tooth derotation, canine and incisor retraction, mild space closure, midline correction, mesial displacement in the posterior quadrants, and traction of impacted teeth. 5,6 According to the length of filament, orthodontics elastomeric chain divided into closed chain, short link chain, medium link chain and long link chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation